Tinjauan Kebutuhan Air Irigasi DI. Pamukkulu Kab. Takalar - Nugraha, Muhammad Agung; Yusuf, Andi Rumpang; Cangara, Satriawati (Jurnal Penelitian Teknik Sipil Konsolidasi, 2024)
The Pamukkulu irrigation area is located in Kab. Takalar with an area of 6005.9 ha where the main water source comes from the Pamukkulu river basin by taking irrigation water from the Pamukkulu Weir, Cakura Weir and Jenemarung Weir. This study aims to analyze the availability of water using reliable discharge (Q80%) using rainfall data using the FJ.Mock method, and to analyze irrigation water requirements in the Pamukkulu irrigation area. The results of the analysis obtained the amount of reliable discharge (Q80%) of 524,06 m3/s with an average reliable discharge of 21,84 m3/s. Meanwhile, the water demand in the Pamukkulu irrigation area is 82,33 m3/sec with an average irrigation water requirement of 3,43 m3/sec. Based on the results of the calculation of the availability of irrigation water to meet the needs of irrigation water, it was concluded that there was a surplus/excess water in meeting the needs of irrigation water in the Pamukkulu irrigation area.